2010
DOI: 10.1523/jneurosci.1491-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The NADPH Oxidase NOX2 Controls Glutamate Release: A Novel Mechanism Involved in Psychosis-Like Ketamine Responses

Abstract: Subanesthetic doses of NMDA receptor antagonist ketamine induce schizophrenia-like symptoms in humans and behavioral changes in rodents. Subchronic administration of ketamine leads to loss of parvalbumin-positive interneurons through reactive oxygen species (ROS), generated by the NADPH oxidase NOX2. However, ketamine induces very rapid alterations, in both mice and humans. Thus, we have investigated the role of NOX2 in acute responses to subanesthetic doses of ketamine. In wild-type mice, ketamine caused rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 63 publications
4
96
0
Order By: Relevance
“…The increase in GSH in this study, suggests enhanced glutamate uptake by the astrocytes, possibly leading to increase in the surface expression of NMDA receptor and glutamate binding for the modulation of dopamine neurotransmission [50]. Therefore, the positive effects of DOX on ketamine-induced schizophrenia-like behavioral phenotypes, further point to mechanisms of action involving antioxidant activities, demonstrated herein and the inherent anti-inflammatory properties [12] [44].…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The increase in GSH in this study, suggests enhanced glutamate uptake by the astrocytes, possibly leading to increase in the surface expression of NMDA receptor and glutamate binding for the modulation of dopamine neurotransmission [50]. Therefore, the positive effects of DOX on ketamine-induced schizophrenia-like behavioral phenotypes, further point to mechanisms of action involving antioxidant activities, demonstrated herein and the inherent anti-inflammatory properties [12] [44].…”
Section: Discussionsupporting
confidence: 52%
“…Oxidative stress increased glutamate levels can inhibit cystine uptake by the cysteine/glutamate exchange system thereby causing intracellular GSH depletion, and consequently poor NMDA surface expression that results in NMDA hypofunctionality [34]; leading to decrease glutamate-dopamine modulations, that is, at least partly, mediated by decreased GSH signaling [49]. Moreover, Behrens et al [45] and Sorce et al [50] previously reported increase in the level of the pro-inflammatory cytokine, interleukine-6 (IL-6) and superoxide producing enzyme, nicotinamide adenine denucleotide phosphate oxidase-2 (Nox-2) in the brain of rodents following repeated administration of ketamine, respectively. Therefore, the increased GSH concentration observed in this study by doxycycline might be mediated through prevention of microglial oxidative burst and inflammatory response elements, thereby enhancing microglial internalization of cysteine intracellularly [51], and cysteine uptake by the cysteine/glutamate exchange system to increase GSH synthesis [52].…”
Section: Discussionmentioning
confidence: 99%
“…This increase in NOX2 was accompanied by an increase in synaptosomal NADPHoxidase activity and paralleled a loss of PV + neurons (19). In another study (280), ketamine caused rapid behavioral alterations, release of neurotransmitters, and brain oxidative stress in wild-type mice; whereas NOX2-deficient mice did not display such alterations. Wild-type mice showed decreased expression of subunit 2A of the NMDA receptor after repeated ketamine exposure, which did not occur in NOX2-deficient mice, implicating NOX2 in down-regulation of NMDA receptor subunits.…”
Section: Diebold Et Almentioning
confidence: 88%
“…Neurons from NOX2-deficient mice showed impaired N-methyl-d-aspartate (NMDA) receptor-dependent long term potentiation (139) and also dysregulation of signaling pathways that are essential to proliferation (61). A study using NOX2-deficient mice also suggests that NOX2-derived ROS control release of the neurotransmitter glutamate in response to specific agonists (280). In hematopoietic cells, low oxygen tension in the bone marrow maintains quiescence and stem cell potential.…”
Section: Other Cell Typesmentioning
confidence: 99%
“…13 although ongoing studies will attempt to elucidate the mechanism behind the effect, swiss biotech GenKyoTex S.A. has iP covering multiple naDPh oxidase (nOX) inhibitors that it believes could yield a nOX2 antagonist to treat schizophrenia. the five isoforms of nOX are responsible for generating superoxides and reactive oxygen species (rOs).…”
Section: Box 1 Nox2-driven Schizophreniamentioning
confidence: 99%